AB0731 Musculoskeletal but Not Skin Disease Activity Influence Rheumatologists Decision To Change Dmards or Biologic Therapy in Psoriatic Arthritis. (15th July 2016) - Porru, G.; Marchesoni, A.; Olivieri, I.; Scarpa, R.; Salvarani, C.; Lubrano, E.; D'Angelo, S.; Piga, M.; Catanoso, M.G.; Peluso, R.; Parsons, W.J.; Mathieu, A.; et al.
Abstract : Background: Psoriatic arthritis (PsA) is a systemic inflammatory disease mainly characterised by arthritis, dactylitis, enthesitis and skin involvement. Recently issued therapeutic guidelines (1) suggest that treatment decisions should be driven by as many manifestations of disease as possible. Objectives: The aim of this study was to determine, in a multicentre Italian cohort of PsA patients, which clinical or patient reported disease outcome influence physician decision to change DMARD or biologic treatment. Methods: 173 consecutive patients with PsA (103 males and 70 females, mean age 52±12 years) were enrolled in a longitudinal observational study. Seven tertiary referral clinics with expertise in PsA and SpA were involved. Detailed clinical examination, including ACR joint count, presence or absence of dactylitis and enthesitis, PASI, were recorded. Patient perception of disease was evaluated by means of global, joint and skin specific VAS scales. Detailed treatment information were also recorded. According to study protocol clinical assessment was performed at baseline and after twelve weeks in order to identify two distinct groups: changed and unchanged DMARD or biologic therapy. Results: A higher number of tender joints (p<0.007) and an higher number of swollen joints (p<0.0003) but not an higher PASI score (p=ns) were observed in the group of patients which were prescribed a change in DMARD or biologic treatment. Enthesitis and dactilytis were more frequent in the group with changes in treatment (p=0.001 and p=0.02 respectively). Patient global and joint perception of disease resulted more severe in the group where a change of therapy was decided, as shown by VAS global (p<0.001) and VAS joint (p<0.02) while no differences in the distribution in the two groups were observed considering patient perception of skin involvement. A significant difference was observed in the following joints: wrist (p=0.05), distal interphalangeal (p<0.002) and knee (p=0.03) involvement. Conclusions: The results of this study, performed in an Italian cohort of PsA patients, suggest that rheumatologists, when they decide to change DMARD or biological treatment in PsA patients, are influenced by both objective evidence of musculoskeletal involvement and by patient reported global and joint outcomes. They do not seem to be influenced by the extent of skin dermatitis, possibly because of the generally low extent of skin involvement in PsA patient and/or because of a musculoskeletal orientated approach of rheumatologists. References: Coates LC, Kavanaugh A, Mease PJ et al. Group for research and assessment of psoriasis and psoriatic arthritis: Treatment recommendations for psoriatic arthritis 2015. Arthritis Rheumatol. 2016 Jan 8. doi: 10.1002/art.39573. [Epub ahead of print] Disclosure of Interest: None declared